Radiological challenges in differentiating Occult Traumatic Pulmonary Hematoma from mediastinal tumor: a case report and literature review - Zhedong Zhang; Yu Huang; Lufeng Zhao; Baiqin Zhao (Journal of Cardiothoracic Surgery)
Abstract Traumatic Pulmonary Hematoma (TPH) is a rare consequence of blunt chest trauma, characterised by lung parenchyma laceration and subsequent hemorrhage. While less common than pulmonary contusions, TPH presents significant diagnostic challenges, particularly when it manifests as Occult Traumatic Pulmonary Hematoma (OTPH) exhibiting subtle or atypical imaging features. We report a case where OTPH was initially misdiagnosed as a posterior mediastinal tumor. A 36-year-old male with a history of minor left chest trauma presented with two oval masses in the right paravertebral region on chest computed tomography (CT). These masses were initially suspected to be mediastinal tumors.Thoracoscopic surgery revealed these lesions to be subpleural tumors in the right lower lobe, which were ultimately diagnosed as pulmonary hematomas (PH). This case highlights the necessity of including PH in the differential diagnosis of intrathoracic masses, especially when imaging findings are ambiguous. Accurate diagnosis often necessitates the integration of clinical history with advanced imaging modalities.